OPTIMALISASI BUFFER ZONE SEBAGAI PENGAMAN PERMUKIMAN DI SEKITAR DEPO TANGKI BAHAN BAKAR MINYAK PT. PERTAMINA PLUMPANG, JAKARTA - Susilo, Udi; Prasidha, I Nyoman Teguh; Dewanto, Wahyu (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
The fuel storage tanks in Plumpang, North Jakarta, owned by PT. Pertamina Tbk. initially had a land area of ​​153 hectares, with the use of 71 hectares as an operational area and the rest as a buffer zone. However, the buffer zone changed its function to a residential area as a place of residence and economic activities for the community which became increasingly dense accompanied by issues of land ownership status. The Plumpang fuel storage tanks fire incident that occurred several times which caused loss of life and property, is a reminder of the importance of a buffer zone that serves as a separating space between areas at risk of flammable material disasters and residential areas. This paper is the result of research on the analysis of the optimization of land requirements for the Plumpang fuel storage tanks buffer zone, by applying quantitative descriptive methods and spatial mapping of the area using Arcgis software, with reference to fuel depot safety standards. It requires the acquisition of 5.2 hectares of land as a buffer zone area in the form of a safe distance from the safety fence wall, construction of a ditch that functions as an accident pool, and re-arrangement of settlements directly adjacent to the buffer zone.